Efficient Synthesis of Diarylmethylamines via Lewis Acid Catalyzed Friedel–Crafts Reactions of Donor–Acceptor Aziridines with N,N-Dialkylanilines - Kim, Yerin; Kwon, Yong Il; Kim, Sung-Gon (Synthesis, 2020)
A method for efficient and mild synthesis of diarylmethylamine scaffold, via Lewis acid catalyzed Friedel–Crafts reaction of donor–acceptor aziridines with N,N-dialkylanilines to afford a biologically important diarylmethylamine derivatives in high yields (up to 88%), is presented. This reaction is suitable for the synthesis of various diarylmethylamine derivatives and has a broad scope for electron-rich arenes, including dimethoxybenzene.
Keywords: diarylmethylamine; Friedel–Crafts reaction; donor–acceptor aziridine; N,N-dialkylaniline; Lewis acid